Gross Anatomical Studies on the Hind Limb of the West African Giraffe (Giraffa camelopardalis peralta) - Kenechukwu T. Onwuama; Sulaiman O. Salami; Esther S. Kigir; Alhaji Z. Jaji (Veterinary Medicine International)
This study on the gross anatomy of the West African giraffe’s hind limb was aimed at investigating the unique morphological features and number of bones making up this region of the skeleton. Two (2) adults obtained as carcasses at different times after postmortem examination were prepared to extract the bones via cold water maceration for use in the study. The appearance of the ossa coxarum and its features presented similarities to that of the horse. However, differences were evident in the convex cranial border of the ilium, small less prominent coxal tuber, and wider interval between the opposite sacral tuber and an oval obturator foramen. Common features reported in most species such as the gluteal line and psoas tubercle were absent. The long femur presented proximally; the greater trochanter connected obliquely via the trochanteric crest to the lesser trochanter. The supracondyloid fossa, obliquely directed medial condyle, and trochlea with two unequal ridges were presented distally. The fibula was absent while the tibia was typical of ruminant presentation with one popliteal line and no muscular lines on its caudal surface. The five (5) tarsals were arranged three proximally and two distally. One (1) metatarsal (3rd and 4th fused) presented two condyles that anchor two (2) digits with 3 phalanges and 3 sesamoid bones each. The total number of bones making up the hind limb was accounted to be 45. In conclusion, this study has provided a baseline data for further biological, archeological, and comparative anatomical studies.